Antiplatelet and Antithrombotic Activity of SL65.0472, a Mixed 5-HT1B/5-HT2A Receptor Antagonist - Berry, Christopher N.; Lorrain, Janine; Lochot, Sylvette; Delahaye, Monique; Lalé, Alain; Savi, Pierre; Lechaire, Irène; Ferrari, Patrice; Bernat, André; Schaeffer, Paul; Janiak, Philippe; Duval, Nicole; Grosset, Alain; Herbert, Jean-Marc; O’Connor, Stephen E. (Thrombosis and Haemostasis, 2001)
The antiplatelet and antithrombotic activity of SL65.0472 (7-fluoro-2-oxo-4-[2-[4-(thieno [3,2-c]pyrin-4-yl) piperazin-1-yl]ethyl]-1,2-dihydroquinoline-acetamide), a mixed 5-HT1B/5-HT2A receptor antagonist was investigated on 5HT-induced human platelet activation in vitro, and in rat, rabbit and canine platelet dependent thrombosis models. SL65.0472 inhibited 5-HT-induced platelet shape change in the presence of EDTA (IC50 values = 35, 69 and 225 nM in rabbit, rat and human platelet rich plasma (PRP)), and also inhibited aggregation induced in human PRP by 3-5 μM 5-HT + threshold concentrations of ADP (0.5-1 M) or collagen (0.3 g/ml) with mean IC50 values of 49 ± 13 and 48 ± 6 nM respectively. SL65.0472 inhibited thrombus formation when given both intravenously 5 min and orally 2 h prior to assembly of an arterio-venous (A-V) shunt in rats as from 0.1 and 0.3 mg/kg respectively. It was active in a rabbit A-V shunt model with significant decreases in thrombus weight as from 0.1 mg/kg i. v. and at 10 mg/kg p. o. The delay to occlusion in an electric current-induced rabbit femoral artery thrombosis model was increased by 251% (p <0.05) after 20 mg/kg p. o. SL65.0472 (30 μg/kg i. v.) virtually abolished coronary cyclic flow variations (7.2 ± 1.0/h to 0.6 ± 0.6/h, p <0.05) and increased minimum coronary blood flow (1.2 ± 0.8 ml/ min to 31.8 ± 8.4 ml/min, p <0.05) in a coronary artery thrombosis model in the anaesthetised dog. Finally, SL65.0472 significantly increased the amount of blood lost after rat tail transection at 3 mg/kg p. o. Thus the anti-5-HT2A component of SL65.0472 is reflected by its ability to inhibit 5-HT-induced platelet activation, and platelet-rich thrombus formation.
Keywords: SL65.0472; 5-hydroxytryptamine; platelet activation; experimental arterial thrombosis